2019
DOI: 10.1002/lt.25383
|View full text |Cite
|
Sign up to set email alerts
|

Gene Silencing With siRNA (RNA Interference): A New Therapeutic Option During Ex Vivo Machine Liver Perfusion Preservation

Abstract: RNA interference (RNAi) is a natural process of posttranscriptional gene regulation that has raised a lot of attention culminating with the Nobel Prize in Medicine in 2006. RNAi‐based therapeutics have been tested in experimental transplantation to reduce ischemia/reperfusion injury (IRI) with success. Modulation of genes of the innate immune system, as well as apoptotic genes, and those involved in the nuclear factor kappa B pathways can reduce liver injury in rodent liver pedicle clamping and transplantation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(43 citation statements)
references
References 58 publications
0
42
0
Order By: Relevance
“…As such, genetic modulation therapies can be administered during MP to improve post-LT outcome. [85][86][87][88] In the future, the development of nanoparticles may be translated into clinical use with the potential to mitigate organ damage through a variety of mechanisms. 89 More studies are needed to address these strategies.…”
Section: Resultsmentioning
confidence: 99%
“…As such, genetic modulation therapies can be administered during MP to improve post-LT outcome. [85][86][87][88] In the future, the development of nanoparticles may be translated into clinical use with the potential to mitigate organ damage through a variety of mechanisms. 89 More studies are needed to address these strategies.…”
Section: Resultsmentioning
confidence: 99%
“…Thijssen et al . have demonstrated that small interfering RNA, together with lipid‐based nanoparticles, successfully silenced the apoptotic gene p53 in a murine NMP model.…”
Section: Perfusion and Re‐conditioning Methods For Abdominal Organsmentioning
confidence: 91%
“…Furthermore, one can be confident that the therapeutic intervention can be successfully delivered to the target organ, without other systemic uptake and associated effects. Thijssen et al [66] have demonstrated that small interfering RNA, together with lipid-based nanoparticles, successfully silenced the apoptotic gene p53 in a murine NMP model.…”
Section: Preservation Of the Livermentioning
confidence: 99%
“…In the case of organ transplantation in particular, ex situ machine perfusion can be an attractive approach for targeted siRNA delivery to the organ during preservation. 8 It prevents filtration by other organs, enzymatic degradation of siRNA in the serum, and off-target effects. In addition, it is clinically more applicable, because RNAi treatment of individual organs can take place after organ procurement, instead of treating the donor systemically.…”
Section: Delivery Strategies For Sirnamentioning
confidence: 99%
“…In the case of organ transplantation in particular, ex situ machine perfusion can be an attractive approach for targeted siRNA delivery to the organ during preservation . It prevents filtration by other organs, enzymatic degradation of siRNA in the serum, and off‐target effects.…”
Section: Introductionmentioning
confidence: 99%